2016
DOI: 10.1038/srep39628
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunization with anti-ActA and anti-listeriolysin O antibodies protects against Listeria monocytogenes infection in mice

Abstract: Listeria monocytogenes is an intracellular pathogen that causes listeriosis. Due to its intracellular niche, L. monocytogenes has evolved to limit immune recognition and response to infection. Antibodies that are slightly induced by listerial infection are completely unable to protect re-infection of L. monocytogenes. Thus, a role of antibody on the protective effect against L. monocytogenes infection has been neglected for a long time. In the present study, we reported that passive immunization with an excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Antibodies are considered irrelevant for protection against L. monocytogenes (Mackaness, 1962 ; Portnoy et al , 2002 ; Asano et al , 2016 ). However, a recent study could demonstrate that pregnancy causes altered glycosylation of IgG.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies are considered irrelevant for protection against L. monocytogenes (Mackaness, 1962 ; Portnoy et al , 2002 ; Asano et al , 2016 ). However, a recent study could demonstrate that pregnancy causes altered glycosylation of IgG.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore wanted to determine the localisation of replicative vs non-replicative bacteria, to determine if non-replicative bacteria were merely those that failed to escape the phagosome. We used phalloidin staining to detect actin ( Figure 1E ) and lysosomal-associated membrane protein 1 (LAMP1) staining ( Figure S1 ) to determine cytoplasmic or phagosomal location, respectively ( 31 36 ). We found that 81% (±5%) of replicative bacteria co-localised with actin and thus were present in the host cell cytoplasm ( Figure 1F ), while 17% (±1%) did not colocalise with actin so were predicted to be localised in phagosomes ( Figure 1G ).…”
Section: Resultsmentioning
confidence: 99%
“…In this aspect, antibodies may offer an interesting alternative to antibiotics in the near future. Indeed, mAbs against Ferritin-like protein (Flp), ActA, or Listeriolysin O (LLO) have shown promising results in protecting mice against Listeria infection ( 50 , 51 ). Thus, the recombinant human mAbs presented here could be an interesting alternative for passive immunization to reduce the number of deaths caused by listeriosis.…”
Section: Resultsmentioning
confidence: 99%